Natural history of Rathke's cleft cysts: A retrospective analysis of a two centres experience. (12th June 2018) - Sala, Elisa; Moore, Justin M.; Amorin, Alvaro; Carosi, Giulia; Martinez, Hector; Harsh, Griffith R.; Arosio, Maura; Mantovani, Giovanna; Katznelson, Laurence
Summary: Objective: Rathke's cleft cyst (RCC) is a common sellar lesion which may cause visual impairment, hypopituitarism and headaches from mass effect. The natural history of these lesions is currently unclear. We investigated the natural history of RCCs and compared surgically treated patients with those treated conservatively. Methods: We performed a retrospective cohort study of patients diagnosed with a RCC between 1996 and 2016 at Stanford University and Ospedale Maggiore Policlinico di Milano. Results: Patients were divided into 2 cohorts: Group A, 72 subjects who underwent surgical resection of a symptomatic RCC, and Group B, 62 subjects managed conservatively. Compared to Group B, Group A subjects had larger RCCs (79% vs 22% had a largest diameter >10 mm, P  < .001) and were more likely (41.5% vs 16%, P  < .001) to present with hypopituitarism and diabetes insipidus (DI) (18% vs 1.6%, P  = .002). In Group A, after a mean follow‐up of 53.7 months, 12.5% of patients had recurrence and a second surgery. After surgery, 35% of patients recovered pituitary function. Hyperprolactinemia (26.6%) and hypogonadism (66.6%) resolved more commonly that did DI (20.1%). New pituitary deficits appeared in 16.6% of patients after surgery. In Group B, with a mean follow‐up of 41 months, only 6.4% had cyst enlargement, none underwent surgery, and none developed a pituitary deficit. Conclusion: Our data offer guidance in decision‐making regarding the management of RCC patients and confirm the safety of conservative treatment in asymptomatic patients.